Trigeminal Herpes Zoster: Early Recognition and Treatment -A Case Report - Upender Malik; Mysore K Sunil; Chandini Gupta; Mamta Kumari (Wolters Kluwer Medknow Publications, 2017)
Herpes zoster is a clinical manifestation of the reactivation of latent varicella zoster virus infection. It is a self-limiting viral infection characterized by painful vesicular eruptions with erythema typically presenting as unilateral dermatomal rash of considerable morbidity, especially in elderly patients. It can be fatal in immunosuppressed or critically ill patients. We present a case of a 52-year-old male who presented with herpes zoster infection involving the V3dermatome, focusing upon early intervention in the management of this condition.